What's wrong with 'deliverology'? Performance measurement, accountability and quality improvement in English secondary education. Issue 4 (4th July 2021) - Gewirtz, Sharon; Maguire, Meg; Neumann, Eszter; Towers, Emma
ABSTRACT: Informed by the ideology of 'deliverology', performance measurement has become a core component of how English schools are held accountable for the quality of their provision. A wealth of research conducted in diverse national contexts where this approach has been influential has suggested that the unintended harms it generates – including a widening of inequalities, a test-driven pedagogic culture and a narrowing of the curriculum – may be outweighing its benefits. In an attempt to circumnavigate such perverse effects, the performance measures used in England have become increasingly sophisticated in recent years, giving them a prima facie plausibility that has led to them being welcomed by some progressive educators as a means of increasing access to high-status knowledge for disadvantaged students. This paper uses data from a survey of English school teachers to interrogate this plausibility. The analysis suggests that when we drill down into the daily life of schools and its underlying logic it becomes increasingly difficult to be comfortable with the progressive defence of the performance measures currently in use; and that, far from improving educational quality, the measures themselves, and the wider deliverology framework with which they are associated, are in certain fundamental respects incompatible with quality improvement.